Current knowledge and attitudes of psychiatric nurses toward electroconvulsive therapy. Issue 4 (28th December 2021) - Ezeobele, Ifeoma E.; Ekwemalor, Chukwudi C.; Pinjari, Omar F.; Boudouin, Genay A.; Rode, Sanjeev K.; Maree, Elizabeth; Russo, Adelyn A.; Selek, Salih
Abstract: Purpose: This study assessed the current knowledge and attitudes of psychiatric nurses toward electroconvulsive therapy (ECT). Design and Methods: A quantitative, nonexperimental study was conducted at a large psychiatric hospital in the United States. The Questionnaire on Attitudes and Knowledge (QuAKE) Scale was used to conduct the assessment among a convenient sample of 158 psychiatric nurses. Findings: Participants' responses to questions that elicited knowledge of ECT ranged from 45% to 99% and positive attitudes ranged from 21% to 96%, revealing increased levels when compared with the low to average knowledge and positive attitudes noted in previous studies. Practice Implications: Targeted ECT education is needed among psychiatric nurses with limited knowledge and negative attitudes toward ECT.